2016
DOI: 10.2118/184393-pa
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Solutions for Spontaneous Imbibition: Fractional-Flow Theory and Experimental Analysis

Abstract: We present analytical solutions for capillary-controlled displacement in one dimension by use of fractional-flow theory. We show how to construct solutions with a spreadsheet that can be used for the analysis of experiments as well as matrix-block-scale recovery in field settings. The solutions can be understood as the capillary analog to the classical Buckley-Leverett solution (Buckley and Leverett 1942) for viscous-dominated flow, and are valid for cocurrent and countercurrent spontaneous imbibition (SI), as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 27 publications
0
53
0
Order By: Relevance
“…This model can be understood as the capillary analog to the classical Buckley-Leverett solution (Buckley and Leverett, 1942) model given the corresponding capillary pressure and relative permeability curves. Recently Schmid et al (2016) compared their calculated results with the experimental measurements of saturation profiles for a water-wet medium, which yielded some good matches. Further reviews can be found in the work by Meng et al (2017).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…This model can be understood as the capillary analog to the classical Buckley-Leverett solution (Buckley and Leverett, 1942) model given the corresponding capillary pressure and relative permeability curves. Recently Schmid et al (2016) compared their calculated results with the experimental measurements of saturation profiles for a water-wet medium, which yielded some good matches. Further reviews can be found in the work by Meng et al (2017).…”
Section: Introductionmentioning
confidence: 91%
“…Recently, Bjørnarå and Mathias (2013) improved the solution using a pseudospectral Chebyshev differentiation matrix. Schmid et al (2011Schmid et al ( , 2013Schmid et al ( , 2016 only focused on spontaneous imbibition and the forced imbibition was not presented in their works.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table provides the initial and boundary conditions for equation . Schmid et al () used the similarity variable ω = x / √ t and presented a general solution in terms of the derivative of a capillary‐driven fractional flow function ( F ) as follows: ω()Sw=2CφFSw, …”
Section: Derivation Of Semi‐analytical Modelmentioning
confidence: 99%
“… F1=BF20.5F3+B2F22+0.25F32+BF2F311Atrue(AF2F32AF22+φt2C20.25emD(),SwσΔSw2, where A=Swln()φt/φiΔSw and B=()3A22()1A are simplifying parameters. Classical approaches, which neglect porosity change ( φ t = φ i ), employ A = 0 and B = − 1; this reduces equation to the definition of capillary‐driven fractional flow term presented by Schmid et al (). In equation , F 1 , F 2 , and F 3 refer to F ( S w ), F ( S w + Δ S w ), and F ( S w + 2Δ S w ), respectively.…”
Section: Derivation Of Semi‐analytical Modelmentioning
confidence: 99%